Optimizing Origin Local Income in Implementing Infrastructure Development in The City of Madiun - Zhanuar Fitri Nor Aisyah; Isharijadi Isharijadi; Elly Astuti (ARISTO, 2022)
This study aims to determine and analyze Regional Original Income in supporting regional development, especially in the field of infrastructure development in Madiun City in 2016-2020, as well as to identify and analyze the supporting and inhibiting factors for optimizing Regional Original Income in Madiun City. The method used is qualitative, using data analysis techniques, namely descriptive analysis with a qualitative approach. From the research results, it can be concluded that: 1) Another Legal PAD is a component of Regional Original Income that has the highest contribution compared to other components in Regional Original Revenue; 2) Personnel expenditures dominate the regional development realization budget; 3) Supporting factors in optimizing Madiun City's Original Regional Revenue include (a) the implementation of a ball pick-up system in which field officers collect taxes and levies, (b) collect data or inventory while the inhibiting factors are (a) awareness of mandatory taxpayers retribution in the importance of paying regional taxes and levies, (b) lack of Human Resources in collecting regional taxes and levies.